Security Technology International Conference, SecTech 2011, Held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings - Kim, Tai-hoon; Adeli, Hojjat; Fang, Wai-chi; Villalba, Javier García; Arnett, Kirk P.; Khan, Muhammad Khurram (Springer eBooks., 2011)
This book comprises selected papers of the International Conferences, SecTech 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focuse on the various aspects of security technology.